2016
DOI: 10.4103/2231-0746.200341
|View full text |Cite
|
Sign up to set email alerts
|

Role of addition of dexamethasone to lignocaine 2% with adrenaline in dental nerve blocks for third molar surgery: A prospective randomized control trial

Abstract: Context:Dexamethasone has been frequently used in oral surgical procedure and accepted by oral and maxillofacial surgeon community worldwide. However, this is the first clinical trial that used dexamethasone as adjuvant with lignocaine in dental nerve block (DNB).Aims:The purpose of this double-blind, randomized control trial (RCT) was to compare the effect of dexamethasone with normal saline (NS) in a lignocaine DNB.Settings and Design:This prospective, double-blind, RCT was carried out after obtaining approv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Smaller fibres are generally more susceptible to LAa because a given volume of LA solution can more readily block the requisite number of sodium channels for impulse transmission to be entirely interrupted. Moreover, several previous studies had reported a statistically significant increase in the mean duration of soft tissue anaesthesia ranging from 197 to 301 minutes (P≤0.05) when dexamethasone was administered locally into the pterygomandibular space after IANB with lignocaine 2% with adrenaline 10,35 . Unfortunately, those studies did not assess perioperative analgesia and VAS and were not well-documented.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Smaller fibres are generally more susceptible to LAa because a given volume of LA solution can more readily block the requisite number of sodium channels for impulse transmission to be entirely interrupted. Moreover, several previous studies had reported a statistically significant increase in the mean duration of soft tissue anaesthesia ranging from 197 to 301 minutes (P≤0.05) when dexamethasone was administered locally into the pterygomandibular space after IANB with lignocaine 2% with adrenaline 10,35 . Unfortunately, those studies did not assess perioperative analgesia and VAS and were not well-documented.…”
Section: Discussionmentioning
confidence: 96%
“…Past studies used dexamethasone adjuvants in long- to intermediate-acting LAa and found significantly prolonged duration of action in brachial and femoral nerve blocks 19 - 26 . Although TMS has been most frequently used for postoperative acute pain studies 9 - 13 , there have not been many investigations conducted to determine the effectiveness of dexamethasone adjuvants with lignocaine in IANB. To the best of our knowledge, this study could be the first to use dexamethasone adjuvants with lignocaine in TMS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, caution is advised as the toxicity also increases [ 21 ]. Deo reported that a supplemental, submucosal injection of dexamethasone at the insertion site of the inferior alveolar nerve block prolongs the duration of anesthesia [ 22 ].…”
Section: Inferior Alveolar Nerve Block Drugsmentioning
confidence: 99%
“…Study found maximum duration of DNB in study group (SG) was 248.88 min and in control group (CG) was 175.44 min. 18 In a study by Zhao et al it was found that perineural dexamethasone prolongs the analgesic duration as compared to intravenous route only when epinephrine is coadministered. Without epinephrine, the two modalities show equivalent effect as adjuvants on regional anesthesia.…”
Section: Perineural Dexamethasonementioning
confidence: 99%